THE INFLUENCE OF INTERPERSONAL COMMUNICATION ON MARRIAGE SATISFACTION OF WOMEN WHO MARRY AT AN EARLY AGE IN NIAS DISTRICT - Harefa, Murni Veronika (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This research aims to see The Influence of Interpersonal Communication on Marital Satisfaction of Women Who Marry at an Early Age in Nias Regency . Based on the discussion of research data analysis conducted on women who married at an early age in Nias Regency, the following conclusions can be drawn: Based on the results of statistical tests carried out by researchers, it can be concluded that Ho is accepted and Ha is rejected, which means that there is no significant influence between Interpersonal Communication and Marital Satisfaction in Women Who Marry at an Early Age in Nias Regency. These results indicate that other factors, such as social and economic pressures, may play a greater role in determining marital satisfaction in this group. Further research is needed to identify these factors and understand how they influence marital satisfaction. From the results of the categorization analysis on the Interpersonal Communication variable, it shows that the overall Interpersonal Communication variable is in the low category with 1 person (1%), in the medium categorization there are 72 people (83%), in the high categorization there are 14 people (16%). From the results of the categorization analysis on the Marital Satisfaction variable, it shows that the overall Marital Satisfaction variable is in the low category as many as 11 people (13%), in the medium categorization as many as 62 people (71%), in the high categorization as many as 14 people (16%). From the results of the T test, the significance of the regression coefficient between the independent variable (Interpersonal Communication) and the dependent variable (Marital Satisfaction) was tested, where the result was t-count < t-table = 0.550 < 1.662, so Ho was accepted and Ha was rejected (no influence).